PENGEMBANGAN LKPD BERBASIS STEM PADA MATERI BANGUN RUANG SISI DATAR SMP KELAS VIII - Putri Perdana Aprilianti; Dwi Astuti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The results of observations of classroom learning and interviews with mathematics teachers in Muhammadiyah 1 Depok Junior High School showed that teaching materials were not available in the form of LKPD, especially STEM-based LKPD. Students as the next generation of the nation must be accustomed to creative and innovative thinking, one of them is by applying STEM-based learning (Science, Technology, Engineering, and Mathematics). This research has the goal of developing STEM-based LKPD on Material of Solid Geometry with Flat Surfacefor to students junior high school in class VIII. The model used in this development is ADDIE. Material expert questionnaire, media expert questionnaire, and student responses questionnaire are instruments used in this study. The product trial subjects in this study were students of Muhammadiyah 1 Depok Junior High School class VIII. Qualitative data analysis and quantitative data analysis are data analysis techniques used in this study. LKPD is declared feasible based on the assessment of media expert, material expert, and students respon. The media expert assessment is in the very either category with average score of 100. The material expert assessment is in the either category with average score 129. The Student questionnaire responses assesment on the quality of learning obtained is in the very either category with average score of 12,23.